2008
DOI: 10.1097/rct.0b013e318123837c
|View full text |Cite
|
Sign up to set email alerts
|

Coronary-to-Bronchial Artery Fistula

Abstract: The incidence of CBF (0.61%) in this study is similar to those of a few cineangiographic studies in the literature. Our study showed that 64-MDCT coronary angiography is an accurate and noninvasive tool for detection of CBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…However, this anastomosis may become enlarged and functional in various cardiovascular and chronic pulmonary diseases with an incidence of about 0.6%. Localized bronchiectasis is the most common condition associated with CBF; however, our three cases the CBFs were combined with pulmonary tuberculosis (2-4, 6). …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, this anastomosis may become enlarged and functional in various cardiovascular and chronic pulmonary diseases with an incidence of about 0.6%. Localized bronchiectasis is the most common condition associated with CBF; however, our three cases the CBFs were combined with pulmonary tuberculosis (2-4, 6). …”
Section: Discussionmentioning
confidence: 63%
“…Most cases of CBF are asymptomatic (2-5). However, the coronary steal phenomenon can cause dyspnea and chest pain, and is currently treated with endovascular embolization or surgical ligation (3-6).…”
Section: Introductionmentioning
confidence: 99%
“…According to a review article from the Netherlands, only 31 such fistulas were reported in the period from 2008 to 2013 [2]. Due to the advanced radiologic techniques that are currently used, such as MDCT, diagnosing coronary-bronchial artery fistula has become less complicated [3,4]. However, the etiology of coronary-bronchial artery fistula is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Said et a l. [2] reported that chest pain was the most frequent symptom (63%) in their review, and Lee et al [4] suggested an association between the coronary steal phenomenon and chest pain in coronary-bronchial artery fistula patients. Hemoptysis (26%) and dyspnea (19%) are also frequent, and otherwise asymptomatic disease occurred in only 5 of 27 subjects (19%) [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation